Zildjian a history of the legendary cymbal makers - Cohan, Jon (Milwaukee, Wis. Hal Leonard, 1999)
"This book, fully authorized by Zildjian, tells the exciting story of the world's most popular cymbal company on the monumental occasion of its 375th anniversary .... The Zildjian story is told firsthand by the Zildjian family members and by the legendary drummers who participated in the important musical movements of the 20th century"--Jacket.
Keywords: Zildjian, Avedis -- 1889-1979.; Avedis Zildjian Company -- History and criticism; Cymbals -- History; Cymbals -- Construction